PENGARUH ROA, ROE, NIM DAN NPM TERHADAP NILAI PERUSAHAAN PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Ainun Khofidotul Fikriyah; M. Mustaqim (FKIP Unswagati, 2024)
Every company must be managed effectively and efficiently to be able to survive and compete. Managing company resources well will provide benefits for the company both internally and externally, this is in accordance with the company's goals. The company's main goal is to improve the welfare of its shareholders by maximizing company profits through company performance, by maximizing company value. The higher the value of the company, the welfare of share owners will increase. This research uses secondary data obtained from the company's annual financial report for the 2020-2022 period which is listed on the Indonesia Stock Exchange and for completeness of data information in the bank's annual report obtained via the bank's website in question. Secondary data is a source of research data obtained by researchers indirectly through intermediary media. The population of this research is banking companies in Indonesia that are listed on the Indonesia Stock Exchange for the 2020-2022 period. Sampling uses the purposive sampling method, according to Umar (2004), the purposive sampling technique is a sample selection technique based on certain characteristics that are considered to have a relationship with previously known population characteristics. The criteria used in determining the sample are banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period, banking companies that publish complete financial reports during the research period, and not in the form of a merger.